Evidence-Based Guidelines for EMS Administration of Naloxone. (2nd November 2019) - Williams, Kenneth; Lang, Eddy S.; Panchal, Ashish R.; Gasper, James J.; Taillac, Peter; Gouda, John; Lyng, John W.; Goodloe, Jeffrey M.; Hedges, Mary
Abstract: The opioid crisis is a growing concern for Americans, and it has become the leading cause of injury-related death in the United States. An adjunct to respiratory support that can reduce this high mortality rate is the administration of naloxone by Emergency Medical Services (EMS) practitioners for patients with suspected opioid overdose. However, clear evidence-based guidelines to direct EMS use of naloxone for opioid overdose have not been developed. Leveraging the recent Agency for Healthcare Research and Quality (AHRQ) systematic review on the EMS administration of naloxone for opioid poisonings, federal partners determined the need for a clinical practice guideline for EMS practitioners faced with suspected opioid poisoning. Project funding was provided by the National Highway Traffic Safety Administration, Office of EMS, (NHTSA OEMS), and the Health Resources and Services Administration, Maternal and Child Health Bureau's EMS for Children Program (EMSC). The objectives of this project were to develop and disseminate an evidence-based guideline and model protocol for administration of naloxone by EMS practitioners to persons with suspected opioid overdose. We have four recommendations relating to route of administration, all conditional, and all supported by low or very low certainty of evidence. We recommend the intravenous route of administration to facilitate titration of dose, and disfavor the intramuscular route due to difficulty with titration, slower time to clinical effect, and potential exposure to needles. We equally recommend the intranasal and intravenous routes of administration, while noting there are variables which will determine which route is best for each patient. Where we are unable to make recommendations due to evidence limitations (dosing, titration, timing, and transport) we offer technical remarks. Limitations of our work include the introduction of novel synthetic opioids after many of the reviewed papers were produced, which may affect the dose of naloxone required for effect, high risk of bias and imprecision in the reviewed papers, and the introduction of new naloxone administration devices since many of the reviewed papers were published. Future research should be conducted to evaluate new devices and address the introduction of synthetic opioids.